CFD based study of fluid flow and heat transfer effect for novel turning tool configured with internal cooling channel. (January 2022) - Singh, Rohit; Sharma, Varun
Abstract: Internal-cooling method due to its numerous advantages has been used during the machining of hard to cut and difficult to machine materials. Cooling channels developed in the cutting inserts, drills, end mills and grinding wheels are used for the heat removal which is concentrated at a smaller region during machining process. So, these cooling channels play a vital role in decreasing the temperature and wear rate of the tools. The heat generation and transfer rate depend upon the physical configuration of the cooling channel. This research work presents novelty in the concept of developing internal cooling channel cutting inserts with different profiles. Three different profiles have been developed to investigate cooling effect on the turning tool insert with different shapes. The results have been compared with the standard tool having no cooling channel. Computational Fluid Dynamics (CFD) has been used to simulate temperature rise for all profiles. A temperature drop of 188 K has been found for internally cooled cutting insert in comparison to the standard tool having no channel. It has also been found that the temperature difference of range 20 K–88 K can be achieved by varying the profile of the channel. Besides this, an increase in the inlet pressure of the cutting fluid has been found to make the coolant profile more efficient in terms of heat removal. Through the velocity vector results, it has been found that with more flow velocity of coolant inside the channel more heat transfer takes place. Turbulence Kinetic Energy (TKE) results showed that the heat transfer rate can be increased with an increase in the TKE value which in turn depends upon the profile of the coolant flow channel. This CFD study in turn has laid the platform for setting the optimum parameters during the turning of Titanium alloy with internal cooling channels. Graphical abstract: Unlabelled Image Highlights: Internal cooling channels have been developed with different profiles inside turning tool. Stress simulation shows maximum stress variation of only 3.8% as compared to cutting insert without channel. Coolant flow through internal channel results in lower temperature as compared to insert without channel. Laminar and turbulent flow of the coolant through the channel have significant role in the temperature drop during simulation of the turning process. Temperature drop is found to be directly proportional to Turbulence kinetic Energy.